Pubertal timing: A life course pathway linking early life risk to adulthood cardiometabolic health. - Maria E Bleil; Bradley M Appelhans; Steven E Gregorich; Robert A Hiatt; Glenn I Roisman; Cathryn Booth-LaForce (PLoS ONE, 2024)
Objective To evaluate a series of prospective life course models testing whether the timing of pubertal development is a pathway through which prepubertal risk factors may influence adulthood cardiometabolic health. Methods Subjects were 655 female participants in the NICHD Study of Early Child Care and Youth Development (SECCYD) and recent SECCYD 30-year follow-up, the Study of Health in Early and Adult Life (SHINE). Prepubertal risk factors included maternal menarcheal age, child race/ethnicity, child health status indicators, and child adversity indicators. Pubertal timing was indexed by breast development onset (Tanner stage [TS] II), pubic hair onset (TS II) and menarcheal age. Adulthood cardiometabolic risk (CMR) was indexed by a composite of waist circumference, systolic blood pressure, diastolic blood pressure, hemoglobin A1c, C-reactive protein, and high-density lipoprotein. Results Inspection of paths between the prepubertal risk factors, pubertal timing indicators, and adulthood CMR composite showed later breast development onset (-0.173, p < .01), later pubic hair onset (-0.182, p < .01), and later menarche (-0.145, p < .01) each predicted lower adulthood CMR, and each pubertal timing indicator mediated effects of prepubertal risk factors on adulthood CMR. Specifically, the timing of breast development onset and menarche mediated effects of maternal menarcheal age, Black (vs. White), Asian/PI (vs. White), child BMI percentile, and child SES on adulthood CMR (all ps < .05), and the timing of pubic hair onset mediated effects of maternal menarcheal age, Black (vs. White), and child BMI percentile on adulthood CMR (all ps < .10). Conclusion Findings in the current study contribute to the broader literature by identifying pubertal development and its timing as a potentially important pathway through which early life exposures may shape adulthood cardiometabolic health and disease. These findings have important implications for novel opportunities for increased surveillance and potential intervention focusing on pubertal development as a target to improve health more broadly.